Light-Intensity-Dependent Expression of Lhc Gene Family Encoding Light-Harvesting Chlorophyll-a/b Proteins of Photosystem II in Chlamydomonas reinhardtii - Teramoto, Haruhiko (American Society of Plant Physiologists, 2002)
Excessive light conditions repressed the levels of mRNAs accumulation of multiple Lhc genes encoding light-harvesting chlorophyll-a/b (LHC) proteins of photosystem (PS)II in the unicellular green alga, Chlamydomonas reinhardtii. The light intensity required for the repression tended to decrease with lowering temperature or CO(2) concentration. The responses of six LhcII genes encoding the major LHC (LHCII) proteins and two genes (Lhcb4 and Lhcb5) encoding the minor LHC proteins of PSII (CP29 and CP26) were similar. The results indicate that the expression of these Lhc genes is coordinately repressed when the energy input through the antenna systems exceeds the requirement for CO(2) assimilation. The Lhc mRNA level repressed under high-light conditions was partially recovered by adding the electron transport inhibitor 3-(3,4-dichlorophenyl)-1,1-dimethylurea, suggesting that redox signaling via photosynthetic electron carriers is involved in the gene regulation. However, the mRNA level was still considerably lower under high-light than under low-light conditions even in the presence of 3-(3,4-dichlorophenyl)-1,1-dimethylurea. Repression of the Lhc genes by high light was prominent even in the mutants deficient in the reaction center(s) of PSII or both PSI and PSII. The results indicate that two alternative processes are involved in the repression of Lhc genes under high-light conditions, one of which is independent of the photosynthetic reaction centers and electron transport events.